Serum and supplement optimization for EU GMP‐compliance in cardiospheres cell culture. Issue 4 (20th January 2014) - Chimenti, Isotta; Gaetani, Roberto; Forte, Elvira; Angelini, Francesco; De Falco, Elena; Zoccai, Giuseppe Biondi; Messina, Elisa; Frati, Giacomo; Giacomello, Alessandro
Abstract Cardiac progenitor cells (CPCs) isolated as cardiospheres (CSs) and CS‐derived cells (CDCs) are a promising tool for cardiac cell therapy in heart failure patients, having CDCs already been used in a phase I/II clinical trial. Culture standardization according to Good Manufacturing Practices (GMPs) is a mandatory step for clinical translation. One of the main issues raised is the use of xenogenic additives (e.g. FBS, foetal bovine serum) in cell culture media, which carries the risk of contamination with infectious viral/prion agents, and the possible induction of immunizing effects in the final recipient. In this study, B27 supplement and sera requirements to comply with European GMPs were investigated in CSs and CDCs cultures, in terms of process yield/efficiency and final cell product gene expression levels, as well as phenotype. B27− free CS cultures produced a significantly reduced yield and a 10‐fold drop in c‐kit expression levels versus B27+ media. Moreover, autologous human serum (aHS) and two different commercially available GMP AB HSs were compared with standard research‐grade FBS. CPCs from all HSs explants had reduced growth rate, assumed a senescent‐like morphology with time in culture, and/or displayed a significant shift towards the endothelial phenotype. Among three different GMP gamma‐irradiated FBSs (giFBSs) tested, two provided unsatisfactory cell yields, while one performed optimally, in terms of CPCs yield/phenotype. In conclusion, the use of HSs for the isolation and expansion of CSs/CDCs has to be excluded because of altered proliferation and/or commitment, while media supplemented with B27 and the selected giFBS allows successful EU GMP‐complying CPCs culture.